2017
DOI: 10.1177/0300060516675111
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two preventive treatments for patients with recurrent miscarriages carrying a C677T methylenetetrahydrofolate reductase mutation: 5-year experience

Abstract: ObjectiveTo investigate the effect of anticoagulant treatment on pregnancy outcomes in patients with previous recurrent miscarriages (RM) who carry a methylenetetrahydrofolate reductase (MTHFR) gene mutation.MethodsIn this longitudinal retrospective study, patients with RM were treated during pregnancy with either: (i) 100 mg/day aspirin and 5 mg/day folic acid (group 1); or the same protocol plus 0.4 mg/day enoxaparin (group 2). An age-matched group of triparous women without RM or thrombophilia was used as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 46 publications
(61 reference statements)
0
18
0
Order By: Relevance
“…Four studies were included in the NOS quality assessment, all of which were cohort studies [42][43][44][45]. A summary of the assessment is presented in the Electronic Supplementary Material (Table S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies were included in the NOS quality assessment, all of which were cohort studies [42][43][44][45]. A summary of the assessment is presented in the Electronic Supplementary Material (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…All studies scored the maximum score of 4 stars in the selection category, indicating that the data used was representative of the targeted community. For the comparability category, one study scored only one star because the authors did not describe any additional baseline characteristics that were well matched between cohorts [42] and the other three studies scored the maximum score of 2 stars [43][44][45]. Finally, in the outcome category, all studies scored the maximum of 3 stars.…”
Section: Resultsmentioning
confidence: 99%
“…Folate (5 mg/day) and aspirin with or without enoxaparin (0.4 mg/day) were administered. The authors observed a much higher delivery rate in the group receiving anti-coagulant (79.7%) in comparison to those receiving only folate and aspirin (46.3%) [84]. Though the exact reason for better efficacy of the treatment regimen incorporating the anti-coagulant could be complex, this may be related to blood clots in fine vasculature as a result of MTHFR mutations and hyper-homocysteinemia [85].…”
Section: Discussionmentioning
confidence: 98%
“…Some other studies have tried different combinations of medicines for RPL management in consultation with MTHFR genotyping. For example, Merviel et al (2017) recruited MTHFR 677C>T mutant females to study their response to treatment. Folate (5 mg/day) and aspirin with or without enoxaparin (0.4 mg/day) were administered.…”
Section: Discussionmentioning
confidence: 99%
“…Research studies notify that HHcy can be generated by the specific mutation in MTHFR. This inherited deficiency lead to a 3.3-fold increase in the risk of miscarriage in a sample group of 185 Caucasian women [32,33]. Literature also specifies that associations between MTHFR C667T mutations to factor V Leiden and prothrombin gene mutations were identified in patients having recurrent miscarriages [34].…”
Section: Miscarriagementioning
confidence: 98%